2020
DOI: 10.3390/su12072990
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Insights for Sustainable Development and Ethical Cohesion: An Empirical Study on Corporate Governance in Romanian Public Entities

Abstract: The global financial crisis was decisive in reanalyzing the role of corporate governance based on the accountability and ethics of governance practices and its impact on sustainable development. The study aims to analyze the relevance of and the interdependencies between financial governance assessment indicators and income efficiency with synergetic effects on sustainable development and social cohesion, offering a distinct contemplation on errors in governance and financial reporting. Deviations concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
(52 reference statements)
1
16
0
1
Order By: Relevance
“…The internal supervision is a complex system, and its degree is often determined by many factors. In order to simplify the evaluation and calculation, this paper draws on the method of comprehensive description of corporate governance (Munteanu et al, 2020). We selected nine indicators (the first largest shareholder's shareholding ratio, the second to fifth largest shareholder's shareholding ratio, the ratio of independent directors, the ratio of institutional investors, whether the chairman and general manager are concurrently, the size of the board of directors, the size of the board of supervisors, the number of boards of directors, the number of boards of supervisors) for principal component analysis.…”
Section: Research Design and Main Modelmentioning
confidence: 99%
“…The internal supervision is a complex system, and its degree is often determined by many factors. In order to simplify the evaluation and calculation, this paper draws on the method of comprehensive description of corporate governance (Munteanu et al, 2020). We selected nine indicators (the first largest shareholder's shareholding ratio, the second to fifth largest shareholder's shareholding ratio, the ratio of independent directors, the ratio of institutional investors, whether the chairman and general manager are concurrently, the size of the board of directors, the size of the board of supervisors, the number of boards of directors, the number of boards of supervisors) for principal component analysis.…”
Section: Research Design and Main Modelmentioning
confidence: 99%
“…The legitimacy to a greater extent empowers the companies in fulfilling mandates and meeting their strategic objectives. However, divergences and disparity in achieving a common understanding can be inversely counterproductive [3]. Inability to have a common front can have unpredictive and substantial effects on the sustainable corporate financial performance, corporate productivity and profitability in all aspects [38,39].…”
Section: Consequences Of Environmentalmentioning
confidence: 99%
“…A couple of the corporate organizations have shown a clear understanding of the essence of legitimacy and the need for adequate environmental accounting information disclosed as required by the shareholders and other stakeholders as a consequence of a necessity of legitimacy theory and its propositions, suggesting that companies interrelated to pollutions must be transparent and in addition, ensure the legitimacy of environmental information disclosure ( [1]; [2]). Legitimacy theory suggested that corporate bodies, especially pollution sensitive companies must endeavour to conduct their operational affairs within the constraints and norms of the society, such that the society will neither be violated nor deprived of its legitimate livelihood [3]. Legitimacy theory suggested that corporate organizations desire to function within the boundaries and norms acceptable by the society, as such, in adopting legitimacy, companies tend to voluntarily report its activities that are required by the stakeholders [4].…”
Section: Introductionmentioning
confidence: 99%
“…Edike and Otuya (2018) submitted that over consumption of paper at home or at office places has huge negative environmental consequences and discarded waste papers equally contribute solid wasted which eventually block drainages and landfill and therefore environmental policy have the potency to guide the management and the board exercising it oversight and monitoring functions. However, on the contrary, Benneth, Schaltergger and Zvesdov (2017); as well as Munteanu, Grigorescu, Condrea and Pelinescu (2020) argued that corporate governance was not interested, committed and do not prioritize environmental policies in its strategic decisions. According to Sulkwowski, Edward and Freeman (2017), the firm size was a factor, as bigger companies guide corporate image and ensure that environmental policies were viewed serious, however, Gul, Mohammad and Rashid (2017) argued that firm size and capital capacity of firm have not affect corporations making efforts to protect the environment.…”
Section: Introductionmentioning
confidence: 99%